2019
DOI: 10.1088/1674-4926/40/12/121801
|View full text |Cite
|
Sign up to set email alerts
|

Deep-ultraviolet integrated photonic and optoelectronic devices: A prospect of the hybridization of group III–nitrides, III–oxides, and two-dimensional materials

Abstract: Deep-ultraviolet integrated photonic and optoelectronic devices: A prospect of the hybridization of group III-nitrides, III-oxides, and twodimensional materials To cite this article: Nasir Alfaraj et al 2019 J. Semicond. 40 121801 View the article online for updates and enhancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 793 publications
(841 reference statements)
0
30
0
Order By: Relevance
“…DUV photodetectors incorporating β‐Ga 2 O 3 thin films have been the subject of extensive studies since the introduction of epitaxial deposition techniques for group III‐oxide materials because they enhance photosensitivity and solar‐blind photodetection characteristics. [ 1–3 ] However, previous research has never investigated the hybrid integration of β‐Ga 2 O 3 on transition metal nitride lattice templates, which offers excellent electrical conductivity and catalytic properties. With respect to optoelectronics, most researchers have so far focused on ultrawide‐bandgap group III‐oxides‐based devices grown and fabricated directly on bulk hexagonal phase alpha‐polymorph aluminum oxide (i.e., α‐Al 2 O 3 or sapphire) substrates, [ 4,5 ] which are suitable for hexagonal phase material epitaxy and suffer from considerably lower thermal conductivity and relatively higher thermal expansion coefficients than other inorganic platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DUV photodetectors incorporating β‐Ga 2 O 3 thin films have been the subject of extensive studies since the introduction of epitaxial deposition techniques for group III‐oxide materials because they enhance photosensitivity and solar‐blind photodetection characteristics. [ 1–3 ] However, previous research has never investigated the hybrid integration of β‐Ga 2 O 3 on transition metal nitride lattice templates, which offers excellent electrical conductivity and catalytic properties. With respect to optoelectronics, most researchers have so far focused on ultrawide‐bandgap group III‐oxides‐based devices grown and fabricated directly on bulk hexagonal phase alpha‐polymorph aluminum oxide (i.e., α‐Al 2 O 3 or sapphire) substrates, [ 4,5 ] which are suitable for hexagonal phase material epitaxy and suffer from considerably lower thermal conductivity and relatively higher thermal expansion coefficients than other inorganic platforms.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to optoelectronics, most researchers have so far focused on ultrawide‐bandgap group III‐oxides‐based devices grown and fabricated directly on bulk hexagonal phase alpha‐polymorph aluminum oxide (i.e., α‐Al 2 O 3 or sapphire) substrates, [ 4,5 ] which are suitable for hexagonal phase material epitaxy and suffer from considerably lower thermal conductivity and relatively higher thermal expansion coefficients than other inorganic platforms. [ 1 ]…”
Section: Introductionmentioning
confidence: 99%
“…When an external voltage is applied to the electrodes, one of the Schottky diodes is biased forward while the other one is biased backward. In between the electrodes on the semiconductor, incident light creates carriers that are drifted by the electric field (which is a pure drift photocurrent) as there is no diffusion component to slow down the device response [6][7][8][9][10][11][12][13][14][15][16][17]. The notion of an MSM-PD was first presented in 1979, and various research groups later reported the actual production of MSM-PDs [6,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The notion of an MSM-PD was first presented in 1979, and various research groups later reported the actual production of MSM-PDs [6,[18][19][20][21]. The MSM-PD has unique characteristics, such as high optical light sensitivity and facile and cost-effective manufacture on a variety of substrates such as Si, SiO 2 , and GaAs, making them an excellent choice for application in current ultra-high-speed communication systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]21,22].…”
Section: Introductionmentioning
confidence: 99%
“…16 Hence, the likelihood of achieving highly efficient AlGaN-based deep-UV surface emitters is severely compromised if we simply employ an Al-rich AlGaN composition. While the exploration of a new material system is one of the possible ways to obtain highly efficient deep-UV devices, [17][18][19][20] developing a new material system and translating the system to an industrial application is non-trivial. Thus, employing novel nanostructures and nanofabrication techniques in an already well-developed technology is more likely to receive industrial adoption to accomplish highly efficient deep-UV emitters.…”
Section: Introductionmentioning
confidence: 99%